Assessment of the psychomotor fitness level of cadet pilots after a 6-month flight training period - pilot study - Wochyński, Zbigniew; Skrzyńska-Rękawek, Justyna; Kobos, Zdzisław (Frontiers in Psychology, 2023)
The aim of the study was to investigate the impact of six-month aviation practice on the improvement of physical fitness and cognitive abilities of cadet pilots. Material and Methods: 20 cadet-pilots (males) with the average age of 22 from Polish Air Force Academy were tested.Two tests of effort were conducted: before (test I) and after (test II) practical flights. Test of physical effort relyed on number of rotations on looping accomplished. When performing rotations on looping, in tests I and II, the percentage level of task performance was assessed using a diagnostic and training device. Tasks for the exerciser were sent wirelessly to the glasses from the operator's position. The heart rate (HR) and blood pressure were measured an camera type Microlife AG.In test II, a statistically significant improvement of percentage of tasks completion (p<0.01) and an insignificant improvement in the performance of rotations on looping compared to test I. After Test I and II demonstrated a statistically significant increase of HR and systolic blood pressure when compared to before test values. Test II illustrated a significant decrease in systolic blood pressure after effort (p<0.05) with regard to test I.The study showed that cadet aviation practice ameliorated their physical fitness and cognitive skills, as well as it helped to diminish their situational stress, which resulted in the decrease in systolic blood pressure after test II.